Synergism of Antimicrobial Frog Peptides Couples to Membrane Intrinsic Curvature Strain - Leber, Regina; Pachler, Michael; Kabelka, Ivo; Svoboda, Irene; Enkoller, Daniel; Vácha, Robert; Lohner, Karl; Pabst, Georg (Biophysical journal, 2018)
Mixtures of the frog peptides magainin 2 and PGLa are well-known for their pronounced synergistic killing of Gram-negative bacteria. We aimed to gain insight into the underlying biophysical mechanism by interrogating the permeabilizing efficacies of the peptides as a function of stored membrane curvature strain. For Gram-negative bacterial-inner-membrane mimics, synergism was only observed when the anionic bilayers exhibited significant negative intrinsic curvatures imposed by monounsaturated phosphatidylethanolamine. In contrast, the peptides and their mixtures did not exhibit significant activities in charge-neutral mammalian mimics, including those with negative curvature, which is consistent with the requirement of charge-mediated peptide binding to the membrane. Our experimental findings are supported by computer simulations showing a significant decrease of the peptide-insertion free energy in membranes upon shifting intrinsic curvatures toward more positive values. The physiological relevance of our model studies is corroborated by a remarkable agreement with the peptide's synergistic activity in Escherichia coli. We propose that synergism is related to a lowering of a membrane-curvature-strain-mediated free-energy barrier by PGLa that assists membrane insertion of magainin 2, and not by strict pairwise interactions of the two peptides as suggested previously.
Keywords: termodynamika; biomechanika; Protein Multimerization; multimerizace proteinu; sekvence aminokyselin; Anti-Bacterial Agents; Magainins; Cell Membrane; Biomechanical Phenomena; Drug Synergism; Stress, Mechanical; Thermodynamics; synergismus léků; Escherichia coli; Amino Acid Sequence; antibakteriální látky; buněčná membrána; mechanický stres; magaininy